Clinical Utility of MMP-9 Expression in Oral Malignant and Premalignant Lesions - Shafiq, Fiza (International Journal of Pathology, 2022)
Introduction: The main histological form of oral cancer is oral squamous cell carcinoma (OSCC) which predominantly arises from oral potentially malignant lesions. Matrix metalloproteinases-9 (MMP-9) can degrade different elements of the ECM and basement membrane. In the present study, MMP-9 expression was assessed in tissue samples among cases of oral squamous cell carcinoma, oral potentially malignant disorders (OPMDs) and healthy individuals to assess its important role in OSCC and OPMDs.Objective: This study aims to assess the immunohistochemical expression of MMP-9 in tissue samples of diagnosed cases of oral squamous cell carcinoma, OPMDs, and normal oral mucosa.Material and Methods: A total of 60 histologically diagnosed cases of OSCC (n=25), OPMDs (n=25), and Healthy individuals (n=10) as control were included. Immunohistochemical staining was performed for all cases. Results were analyzed using SPSS version 20.Results: Increased expression of MMP-9 was observed in OSCC cases (n=23/25; 92%) as compared to OPMDs and healthy individuals. Statistically, a significant relation was observed while comparing the grade of staining intensity and MMP-9 expression among OSCC cases (p=0.001) and OPMD cases (p= ≤ 0.01).Conclusion: Increased expression of MMP-9 was observed in OSCC as compared to OPMDs and healthy individuals. Evaluation of MMP-9 could be of clinical importance in OSCC and can be used as a diagnostic marker of OSCC and OPMDs